A revision of the family Thismiaceae (Dioscoreales) in Cambodia, Laos and Vietnam - Nuraliev, Maxim S.; Yudina, Sophia V.; Truong, Ba Vuong; Do, Thi Xuyen; Luu, Hong Truong; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P. (Phytotaxa, 2020)
We present the first taxonomic account of the family Thismiaceae in the countries of Eastern Indochina. A single genus of Thismiaceae, Thismia, with eight species is known to inhabit this region. Six species, including four national endemics, are found in Vietnam, whereas Cambodia and Laos each has a single and endemic species of Thismia. We report new records of a number of species, which allowed us to establish for the first time their distribution areas. We show geographical distribution of all species of Thismia in Cambodia, Laos and Vietnam on a map. We recognise Hon Ba Nature Reserve and Chu Yang Sin National Park as hotspots of known Thismia diversity in Eastern Indochina. We confirm the presence of T. javanica in Vietnam, earlier known as a doubtful report, by specimen investigation. We significantly amend morphological descriptions of several Vietnamese species. We highlight a number of characters with remarkable intraspecific variation, along with the most important structural differences between morphologically similar species. We discuss remaining taxonomic problems of Indochinese Thismia, and present an identification key to species of Thismiaceae in Cambodia, Laos and Vietnam.